AN EMPIRICAL INVESTIGATION INTO THE DEMOGRAPHIC DETERMINANTS OF RESEARCH BEHAVIORS AMONG ACADEMICS IN TERTIARY INSTITUTIONS IN CROSS RIVER STATE, NIGERIA (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2025)
This study explores the demographic determinants influencing research behaviors among academics in tertiary institutions in Cross River State, Nigeria. Utilizing a cross-sectional survey design, data were collected from 384 academics across universities, polytechnics, and colleges of education using a structured questionnaire. The findings reveal that age, gender, educational level, academic rank, and institutional type significantly shape research productivity, collaboration, and dissemination practices. Younger academics (aged 30–40) and those with doctoral degrees exhibited higher research output, while gender disparities showed male academics publishing more frequently than females. Institutional support, such as access to research facilities and funding, also emerged as a critical factor. The study highlights the need for targeted interventions to address gender inequities and enhance research infrastructure to boost academic productivity. Recommendations include capacity-building programs, gender-sensitive policies, and increased funding to foster a vibrant research culture. These findings contribute to understanding the dynamics of research behaviors in resource-constrained settings, offering insights for policymakers and institutional leaders.